Cheiropathy in Diabetic Children. Kinesi- and Physiotherapy - A.E. Abaturov; L.L. Petrenko; D.V. Logvinov; N.A. Beletskaia; N.N. Lybenko; N.A. Kozlova (Zaslavsky O.Yu., 2016)
The charts of 240 patients were analyzed and 95 type 2 diabetic children were observed. the diabetic cheiropathy was found to develop in one third patients with type 1 diabetes mellitus not older than 9 years old. Cheiropathy was associated with neuropathy, retinopathy and nephropathy development and may be a phenotypic marker for these complications development in type 1 diabetic patients. Kinesitherapy and electrophoresis with potassium iodide can improve impaired fingers mobility in 80.2 % children with type 1 diabetes mellitus.